Response of Direct-seeded Rice (Oryza sativa L.) to Varying Levels of Nitrogen and Phosphorus on Yield, Nutrient Uptake and Soil Nutrient Status in Nagaland - Seyiekevino Tsukru; P.K. Singh; Mercy Vanlalhmangaihi; Lanamika Kjam (Journal of the Indian Society of Soil Science, 2023)
A field experiment was carried out to study the response of direct-seeded rice to varying levels of nitrogen (N) and phosphorus (P) on yield, nutrient uptake and soil nutrient status under Nagaland conditions during the kharif period i.e., June-October 2018, in the experimental research farm of the School of Agricultural Sciences and Rural Development, Nagaland University, Nagaland, India. The experiment was carried out with three levels of N (0, 50 and 100 kg N ha-1) and three levels of P (0, 40 and 80 kg P2O5 ha-1) making a total of nine treatments in combination laid out in a RBD design. Results from the study revealed that application of N at 100 kg ha-1 significantly increased the grain and stover yield to an extent of 61.9 and 37.7 per cent over control and 40 kg P2O5 ha-1 recorded 25.8 and 13.9 per cent over control. Likewise, combination of treatment T8 (100 kg N: 40 kg P2O5) augmented the grain and stover yield to an extend of 135.0, 64.6 per cent over the control. Nutrient (NPK) uptake by the crop was significantly influenced with the higher nutrient levels where 50 kg N ha-1, 40 kg P2O5 ha-1 and T8 performed significantly better than the rest of the treatments, while levels P2 and P1 remained at par with each other for some parameters. Application of nitrogen at 100 kg ha-1 and phosphorus at 40 kg ha-1 significantly increased the soil OC, available NPK to a great extent over the control under Nagaland conditions.